Assistance in Developing Integrated Teaching Modules on Al-Islam and Muhammadiyah Values in the Independent Curriculum Era as Strengthening Islamic Education - Zein, Syaikha Dziyaulhaq; Dumono; Wibowo, Agus Wahyu; Widyastuti, Rini; Siswanto, Deny Hadi; Pisriwati, Siti Atwano (Jurnal Pengabdian Masyarakat Bestari, 2025)
This activity aims to help teachers develop teaching modules that are integrated with the values of Al-Islam and Muhammadiyah and in accordance with the Learning Outcomes in the Independent Curriculum. This activity was held at SMA Muhammadiyah Mlati in September 2024 with 18 teachers as participants, the methods used included socialization, workshops, and mentoring. Socialization provides an understanding of integrated modules, workshops equip teachers with skills to develop them, and mentoring supports the integration of Al-Islam and Muhammadiyah values. This activity also includes the inclusion of verses of the Quran and related Hadiths. As a result, teachers gain new knowledge and skills, and are advised to be more active in developing the module.